The role of the World Trade Organization in the international anti-corruption movement - Gundani, Melissa Memory (Department of Commercial Law, 2015)
Corruption adversely affects various aspects of economic activity, including international trade. As corruption affects international trade in a number of ways, various countries and international organisations have made co-ordinated efforts to effectively control corruption in general and in the context of international trade. Despite the World Trade Organization's role as a body for making and enforcing international trade rules, it has not actively participated in the fight against corruption in the trade arena. This paper explores why the World Trade Organization has made no anti-corruption initiatives and provides a review of the current role that is played by the organization in the international anti-corruption movement, through its existing framework. The study also includes a review of the different instruments put in place by other organisations and countries that have actively participated in combating corruption in international trade, and whether the World Trade Organization should follow-suit.